2019
DOI: 10.5194/acp-19-603-2019
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of surface ozone simulation among selected regional models in MICS-Asia III – effects of chemistry and vertical transport for the causes of difference

Abstract: Abstract. In order to clarify the causes of variability among the model outputs for surface ozone in the Model Intercomparison Study Asia Phase III (MICS-Asia III), three regional models, CMAQ v.5.0.2, CMAQ v.4.7.1, and NAQPMS (abbreviated as NAQM in this paper), have been selected. Detailed analyses of monthly averaged diurnal variation have been performed for selected grids covering the metropolitan areas of Beijing and Tokyo and at a remote oceanic site, Oki. The chemical reaction mechanism, SAPRC99, used i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 47 publications
1
28
0
Order By: Relevance
“…O 3 concentrations slowly increased with height in M8 and M11, but they mixed well in the planetary boundary layer (PBL) and decreased from 800 to 700 hPa in the other models. Akimoto et al (2019) found that the parameterization on downward O 3 transport from the upper boundary layer contributed considerably to discrepancies between M1, M6 and M11. In EA2, vertical structures of O 3 among models were found to be consistent, but concentrations differed more than those in EA1.…”
Section: Vertical Profiles Of Omentioning
confidence: 96%
See 2 more Smart Citations
“…O 3 concentrations slowly increased with height in M8 and M11, but they mixed well in the planetary boundary layer (PBL) and decreased from 800 to 700 hPa in the other models. Akimoto et al (2019) found that the parameterization on downward O 3 transport from the upper boundary layer contributed considerably to discrepancies between M1, M6 and M11. In EA2, vertical structures of O 3 among models were found to be consistent, but concentrations differed more than those in EA1.…”
Section: Vertical Profiles Of Omentioning
confidence: 96%
“…The EANET was launched in 1998 to address acid deposition problems in East Asia, following the model of the Cooperative Program for Monitoring and Evaluation of the Long-Range Transmission of Air Pollutants in Europe. In this study, eight remote stations in the northwestern Pacific and Japan (EA3 subregion) were selected to evaluate model performance levels for the downwind regions of the Asian continent (Ban et al, 2016). More information on the EANET can be found at http://www.eanet.asia/ (last access: 8 October 2019).…”
Section: Observational Data For Omentioning
confidence: 99%
See 1 more Smart Citation
“…where WD model is the original modeled wet deposition and P model and P observation are the modeled and observed precipitation amounts, respectively. This approach has been used in previous studies over the US (Appel et al, 2011;Zhang et al, 2018) and Asia (Itahashi, 2018). Note that this precipitationadjusted approach assumes that errors associated with the modeled precipitation are linearly related to errors in wet deposition amounts and the precipitation was adjusted by the total amount of observed precipitation; hence, the modeled convective and subgrid-scale precipitation was not distinguished.…”
Section: Precipitation-adjusted Approachmentioning
confidence: 99%
“…This phase consists of three parts: topic 1, the comparison and evaluation of current multiscale air quality models; topic 2, the development of reliable emission inventories in Asia; and topic 3, the interactions between air quality and climate change. Scientific papers focusing on gas-phase species (Kong et al, 2020), aerosols (Chen et al, 2019), and ozone (O 3 ) (Akimoto et al, 2019;Li et al, 2019) have been published. The details of topic 2 (Li et al, 2017a) and topic 3 (Gao et al, 2018) have also been reported.…”
Section: Introductionmentioning
confidence: 99%